Strategi pegembangan ternak babi melalui Program Pembangunan Desa Mandiri (PPDM) di Kabupaten Nabire - Alouisius Rahangiar; Sangle. Y. Randa; Stepanus Pakage (Cassowary, 2022)
The strategy for developing pigs through this research is a pilot model for the assistance of the Program Pembangunan Desa Mandiri (PPDM) in Nabire Regency. The objectives of this research are: to determine the factors that influence the pig farming business in Nabire Regency, to determine the strategy of developing pigs for farmers and the Animal Husbandry Office of Nabire Regency, to evaluate the pig farming development program and to recommend a model for developing pigs in Nabire Regency.The research was analyzed by swot analysis and multiple linear regression analysis. This research was conducted for 1 month on 30 respondents from pig farmers and 5 respondents from program actors. The results of the research through SWOT analysis showed that based on the sum of the total scores on the IFE and EFE matrices, the scores were 2.41 and 2.55, respectively. The IE matrix value indicates the position of the middle cell (Growth/Stable). Based on the results of the calculations in the QSP matrix, the most appropriate strategy to implement is to increase the productivity of pigs 6.10. The results of the study through the analysis of Multiple Linear Regression, it is known that the coefficient of determination test results show the R2 value of the regression model is 89.40%. This shows the ability of the independent variables together to contribute to the dependent variable by 89.40%. Based on the F-test that together the independent variables affect the production of pigs. Based on the t-test in this study, it is known that all variables included in the model separately have no effect on pig production.